Keyhole - Maddin, Guy 1956-; Toles, George E.; Shapiro, Jody ca. 20. Jh; Du Toit, Jean Jacques; Patric, Jason 1966-; Rossellini, Isabella 1952-; Kier, Udo 1944- (Monterey Media, Inc., 2012)
In a house haunted with memories, gangster and father Ulysses Pick arrives home after a long absence towing the body of a teenage girl and a bound and gagged young man. His gang waits inside his house, having shot their way past police. There is friction in the ranks. Ulysses, however, is focused on one thing: journeying through the house, room by room, and reaching his wife Hyacinth in her bedroom upstairs. His odyssey becomes an emotional tour as more is revealed about the Pick family
Originally produced as a motion picture in 2011. - Special features include short film, Send me to the lectric chair and F-hole, the music behind keyhole by Jason Staczek, trailer
Originally produced as a motion picture in 2011
Keywords: Gangsters / Drama; Supernatural / Drama; Supernatural -- Drama.; Gangsters -- Drama.; Horrorfilm; Gangster; Das Übernatürliche; Film; DVD-Video